Impact of Diabetes on Short-Term Outcomes in STEMI Patients Undergoing Primary Percutaneous Coronary Intervention (PCI): Diabetes and Short-Term Outcomes in STEMI Patients Undergoing PCI - Maaz, Hafiz Muhammad; Iqbal, Zafar; Gul, Sabahat e (Pakistan Journal of Health Sciences, 2025)
Diabetes mellitus is a major global health issue, significantly increasing the risk of morbidity and mortality, especially after myocardial infarction. Objectives: To assess the impact of diabetes on short-term outcomes in STEMI patients treated with primary PCI. Methods: This comparative cross-sectional study enrolled 200 patients undergoing elective coronary angiography at Shahida Islam Medical Complex, Lodhran, using non-probability consecutive sampling. Qualitative variables, such as gender and hypertension, were summarized as frequencies, while quantitative variables, including age, BMI, and HbA1c, were expressed as mean ± standard deviation (SD). Outcomes, including stroke, arrhythmia, renal failure, and mortality, were compared using the Chi-square test, whereas changes in serum creatinine were analyzed with independent t-tests. Statistical significance was set at p < 0.05. Data were collected using a structured proforma and analyzed using SPSS version 21.0. The combined effect of categorical variables was calculated and reported as risk ratios with 95% confidence intervals. Results: Diabetic patients were older and had a higher prevalence of hypertension, smoking, and prior ischemic heart disease (IHD). They showed significantly worse short-term outcomes, including higher rates of stroke (5.6%, p=0.04), renal failure (11.1%, p=0.02), and mortality (10.0%, p=0.03) compared to non-diabetics. Conclusions: There are worse short-term outcomes possibly related to diabetes mellitus in STEMI patients undergoing PCI, particularly for stroke, renal failure, and mortality. These findings highlight the need for aggressive management of diabetic patients presenting with STEMI.